Development of Electronic Learner Worksheets with Live worksheets on Lithospheric Dynamics Material for High School Students - Desy Andri Tri Palupi; Sri Kantun; Elan Artono Nurdin; Slamet Agus Wahyudi (JPG (Jurnal Pendidikan Geografi), 2023)
This research aims to develop learning products in the form of electronic student worksheets with live worksheets on lithospheric dynamics material in class X at Senior High School which has eligibility standards. The research method used is R&D (Research and Development) research with the ADDIE model which consists of analysis, design, development implementation and evaluation stages. The analysis stage includes performance analysis, needs analysis, curriculum analysis, student analysis. The design stage includes making learning devices, product design, and preparing research instruments. The development stage is determining the media used, validation, and revision. The implementation stage is the stage of implementing the E-LKPD that has been developed in a real situation in the classroom. The final stage is the evaluation stage which is carried out to analyze errors during data collection and can be done in each of the four stages above. This research was conducted at Senior High School Number 1 Jember with the research trial subjects were students of class X5 as many as 36 students. The research instruments used were validation sheets and student response questionnaires. The results showed that electronic student worksheets with live worksheets were feasible with a percentage achievement of 97.5% in the material aspect, 95.8% in the design aspect, 100% in the language aspect and 88%. overall assessment by geography learning practitioners.Â  The implementation of the E-LKPD trial required 2x meetings or 4 x 45 minutes of class time on January 11 and 18, 2022.Â  The results of student responses get very good criteria with an average percentage of 91.2%. From these data it can be concluded that the products developed are declared feasible and very good for use in learning geography, especially in high school lithospheric dynamics material.